Five Poems by Derek Mahon - Mahon, Derek; Eiroa Guillén, Ana; Hughes, Brian (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1989)
October (from Antarctica) ; Death and the sun (from Antarctica) ; Matthew V, 29-30 (from Poems 1962-1978) ; The apotheosis of tins (from Poems 1962-1978) ; The hunt by night (from The hunt by night) = Octubre ; El sol y la muerte ; San Mateo V, 29-30 ; La apoteosis de las latas ; La cacería nocturna / traducción de Ana Eiroa Guillén y Brian Hughes